Conserved metabolic enzymes as vaccine antigens for giardiasis - Sozaburo Ihara; Yukiko Miyamoto; Christine H. Y. Le; Vivien N. Tran; Elaine M. Hanson; Marvin Fischer; Kurt Hanevik; Lars Eckmann (Public Library of Science (PLoS), 2022)
Giardia lamblia is a leading protozoal cause of diarrheal disease worldwide. Infection is associated with abdominal pain, malabsorption and weight loss, and protracted post-infectious syndromes. A human vaccine is not available against G. lamblia. Prior studies with human and murine immune sera have identified several parasite antigens, including surface proteins and metabolic enzymes with intracellular functions. While surface proteins have demonstrated vaccine potential, they can exhibit significant variation between G. lamblia strains. By comparison, metabolic enzymes show greater conservation but their vaccine potential has not been established. To determine whether such proteins can serve as vaccine candidates, we focused on two enzymes, α-enolase (ENO) and ornithine carbamoyl transferase (OCT), which are involved in glycolysis and arginine metabolism, respectively. We show in a cohort of patients with confirmed giardiasis that both enzymes are immunogenic. Intranasal immunization with either enzyme antigen in mice induced strong systemic IgG1 and IgG2b responses and modest mucosal IgA responses, and a marked 100- to 1,000-fold reduction in peak trophozoite load upon oral G. lamblia challenge. ENO immunization also reduced the extent and duration of cyst excretion. Examination of 44 cytokines showed only minimal intestinal changes in immunized mice, although a modest increase of CCL22 was observed in ENO-immunized mice. Spectral flow cytometry revealed increased numbers and activation state of CD4 T cells in the small intestine and an increase in α4β7-expressing CD4 T cells in mesenteric lymph nodes of ENO-immunized mice. Consistent with a key role of CD4 T cells, immunization of CD4-deficient and Rag-2 deficient mice failed to induce protection, whereas mice lacking IgA were fully protected by immunization, indicating that immunity was CD4 T cell-dependent but IgA-independent. These results demonstrate that conserved metabolic enzymes can be effective vaccine antigens for protection against G. lamblia infection, thereby expanding the repertoire of candidate antigens beyond primary surface proteins. Author summary Giardia lamblia is a leading parasitic cause of diarrheal disease worldwide. Symptomatic infection is associated with abdominal pain, malabsorption and weight loss, and can lead to protracted post-infectious syndromes. Despite its medical importance, a human vaccine has not been developed against the pathogen. Here we show that two highly conserved enzymes with metabolic functions in the cytoplasm of the parasite can be used as antigens for effective vaccines against G. lamblia, thereby significantly expanding the repertoire of candidate antigens against this clinically important infection beyond primary surface proteins.